2020
DOI: 10.1186/s10020-020-00148-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the transcription factor TFAP2D is associated with aggressive tumor phenotype in prostate cancer lacking the TMPRSS2:ERG fusion

Abstract: Background: TFAP2D is a transcription factor important for modulating gene expression in embryogenesis. Its expression and prognostic role in prostate cancer has not been evaluated. Methods: Therefore, a tissue microarray containing 17,747 prostate cancer specimens with associated pathological, clinical, and molecular data was analyzed by immunohistochemistry to assess the role of TFAP2D. Results: TFAP2D expression was typically increased in prostate cancer as compared to adjacent non-neoplastic glands. TFAP2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Recently, we examined the role of WWOX in conjunction with two interacting proteins, which together orchestrated biological processes diversely in BLCA depending on their cellular level [8]. These were two Activating Enhancer-Binding Protein 2 (AP-2) Transcription Factors (TFs), AP-2α and AP-2γ, members of the AP-2 family, whose natural function is related to early development regulation [9], but which are also involved in carcinogenesis [10][11][12][13][14], including BLCA [15][16][17]. AP-2α and AP-2γ have distinct roles in different tumors, and tend to play an anti-cancer or tumor-promoting role, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we examined the role of WWOX in conjunction with two interacting proteins, which together orchestrated biological processes diversely in BLCA depending on their cellular level [8]. These were two Activating Enhancer-Binding Protein 2 (AP-2) Transcription Factors (TFs), AP-2α and AP-2γ, members of the AP-2 family, whose natural function is related to early development regulation [9], but which are also involved in carcinogenesis [10][11][12][13][14], including BLCA [15][16][17]. AP-2α and AP-2γ have distinct roles in different tumors, and tend to play an anti-cancer or tumor-promoting role, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a significant fraction of PCa patients, CTCF showed high expression and was associated with tumor aggressiveness (high Gleason grade, advanced tumor stage, lymph node metastasis, early biochemical recurrence, as well as accelerated cell proliferation) (details are given in [ 45 ]). For TFAP2D, we observed that the TFAP2D level was high in about 75% of the patients with poorer clinical course, details see [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…As reported recently, we identified the CCCTC-binding factor (CTCF) as a good prognostic marker specifically for patients with ERG-negative PCa [ 45 ]. IHC staining of TFAP2D (details, see [ 44 ]) and IRF1 showed that both transcription factors also suited as prognostic markers for PCa. For the predicted direct regulators MITF and BHLHE40, the immunohistochemical staining did not work in our assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latest data regarding contribution in cancer indicates that AP-2β overexpression has been found to promote tumor growth in both breast and thyroid cancer and predicted poor prognosis or tumor progression, respectively [37,38]. Finally, although little is known of AP-2δ and AP-2ε, the former is thought to be associated with progression and genomic instability of prostate cancer while the latter acts as a tumor suppressor in neuroblastoma [39,40].…”
Section: Introductionmentioning
confidence: 99%